Rekonseptualisasi Prinsip Tabayyun sebagai Kerangka Etika Komunikasi Organisasi dalam Menghadapi Disinformasi Digital: Tinjauan Literatur Sistematis - M. Faisal Hasrimy; Hasnun Jauhari Ritonga (CV. Ulil Albab Corp, 2026)
: This study aims to map the development of digital disinformation studies and organizational communication ethics, analyze the relevance of the tabayyun principle in the perspective of contemporary organizational communication, and formulate a conceptual model of tabayyun-based organizational communication ethics. The study uses a qualitative approach with a Systematic Literature Review (SLR) design referring to the PRISMA protocol. Data were obtained from journal articles indexed in international databases such as Scopus, Web of Science, ProQuest, DOAJ, and Google Scholar over the past ten years. The analysis was conducted through thematic analysis to identify relevant patterns, themes, and conceptual synthesis. The results of the study indicate that: 1) Digital disinformation literature has shifted from a descriptive-typological approach to a normative-ethical approach, but it is still fragmented and has not integrated the value of normative verification based on Islamic tradition; 2) The tabayyun principle has strong theoretical relevance because it contains an epistemic dimension (information verification), a moral dimension (communicative responsibility), and an institutional dimension (value-based organizational culture); and 3) This study formulates a conceptual model of tabayyun-based organizational communication ethics that places verification, moral integrity, and institutionalization of values as the foundation of organizational communication governance. This model contributes theoretically by integrating digital disinformation theory, information ethics, and organizational communication, and provides practical implications for strengthening a culture of preventative communication in facing the challenges of digital disinformation in the era of global communication transformation